Small bowel gastrointestinal stromal tumor presenting with gastrointestinal bleeding in patient with type 1 Neurofibromatosis: Management and laparoscopic treatment. Case report and review of the literature. (February 2021) - Mandalà, S.; Lupo, M.; Guccione, M.; La Barbera, C.; Iadicola, D.; Mirabella, A.
Highlights: A multidisciplinary team is mandatory for the correct management of hemorrhagic GIST and its complications. There is a well-known association between type 1 Neurofibromatosis and GIST. Type 1 Neurofibromatosis-GIST and sporadic GIST have different behaviour. In case of localised and resectable GIST surgical treatment is the mainstay. Laparoscopic approach, if performed correctly, is safe and effective with better short-term outcomes then open surgery. Abstract: Introduction and importance: Gastrointestinal stromal tumor (GIST) is the most common mesenchymal neoplasm of the gastrointestinal tract. It may be asymptomatic; nevertheless, gastrointestinal bleeding is the most frequent symptom, due to mucosal erosion. Its poor lymph node metastatic spread makes GIST often suitable of minimally invasive surgical approach. The importance of this study is to increase the awareness among physicians about this condition in particular scenarios as in our case and to stress the role of laparoscopic surgery. Case presentation: A 74-year-old female patient presented to the emergency department with hematemesis, followed by haematochezia and melena. The patient had a medical history of type 1 Neurofibromatosis (NF1). She underwent, after CT scan, esophagogastroduodenoscopy, and endoscopic haemostasis. Finally, we performed a laparoscopic resection of a mass of the first jejunal loop. The postoperative period was predominantly uneventful. Pathological examination confirmed a low-risk GIST. Clinical discussion: Proximal jejunal GIST may cause an upper and lower gastrointestinal bleeding. A multidisciplinary team approach is mandatory for the correct management of this disease and its complications (bleeding). GISTs are indicated as the most commonly gastrointestinal NF1 associated tumours. In case of localised and resectable GIST surgical treatment is the mainstay and laparoscopic surgery is a valid alternative. Conclusion: In case of abdominal bleeding mass in a NF1 patient, it is important to keep in mind the well-known association between NF1 and GIST to facilitate the diagnosis and to quickly perform the appropriate treatment. Laparoscopic approach is safe and effective if the oncological radicality is respected.